Quality of life in patients with pressure injuries (Research, Society and Development, 2021)
Objective. The present work aims to reflect on the quality of life in patients with pressure injuries. This writing is bibliographical in nature, as the proposal presented was investigated in scientific articles (GIL, 2011) for a better understanding of the research topic. Methodology. Thus, the following authors were used as authors: Portugal and Christovam (2018); Rodrigues and Soriano (2011); Moro and Caliri (2016) among others and others. Results. In addition, through the literature and systematic review, it was possible to perceive the barriers experienced by patients with pressure injuries, their incidence, among other markers that greatly affect the quality of life of these injured people (a), thus proposing solutions to improve their condition. clinical, as well as the sharing of information for the same and their family, and this becomes possible when (a) health professionals establish a clear, informative and objective language on the subject. In this sense, they (a) must have continued training on the theme-generator, as well as courses, readings, debates, among other means of exchanging knowledge. Conclusion. Therefore, their quality of life is notorious when there is equity in health care.